Material Design Experiences of Turkish Teacher Candidates - KÖKÇÜ, Yelda (T.C. Milli Egitim Bakanligi, 2025)
The use of materials in the teaching-learning environment provides users with conveniences in terms of concretizing information, creating a fun classroom environment, increasing the permanence of information, providing the opportunity to learn by doing and experiencing, and supporting the effective use of basic language skills. It is aimed to achieve these aims through the “Material Design in Turkish Teaching” course, which is one of the elective courses in the Turkish teaching undergraduate program. The aim of this study is to present examples of the materials prepared by candidate Turkish teachers within the scope of Material Design in Turkish Language Teaching course and to determine the opinions of the students about the course. The study was conducted with a total of 22 students studying in the Turkish language teaching department of a state university in the fall semester of the 2023-2024 academic year.The study was conducted in a phenomenological type of qualitative research designs, and a semi-structured interview form was used as a data collection tool. The data were analyzed according to the content analysis technique using MAXQDA qualitative data analysis software. In addition, examples of the materials prepared by the students during the course are presented. According to the results of the study, it was determined that pre-service teachers generally had positive opinions about the use of materials in Turkish lessons, but they had difficulties in the stages of the material design process such as decision making, producing original materials and designing. © (2025), (T.C. Milli Egitim Bakanligi). All rights reserved.
Türkçe Öğretmeni Adaylarının Materyal Tasarlama Deneyimleri
Keywords: Material design; Materyal tasarımı; pre-service teachers; teaching material; Turkish language teaching; Türkçe öğretimi; öğretim materyali; öğretmen adayları